The history of verse studies and formalism - Boris V. Orekhov (Слово.ру: балтийский акцент)
The core idea of formalism is that literature is not merely a function of psychology or social theory and cannot be explained using the tools of these sciences. One could say that poetics is almost the only philological subdiscipline that has managed to preserve the fundamental idea of formalism, explaining poetic facts in terms of poetics itself, rather than through economic, sociological, or psychological means. This is precisely the approach taken by Mikhail Gasparov in his article on the history of Russian rhyme, where, without resorting to reductionism, he constructs his concept of cultural history as a sequence of crises and their resolutions. Maxim Shapir, in his well-known work on the evolution of the Russian iambic tetrameter, specifically highlights the unusual method he employs—the explanation of a poetic fact through historically documented and socially significant events. Poetics, more than any other branch of literary studies, maintains its hermetic nature, which presupposes the explanation of literary data through literary circumstances. The situation in which literature finds itself having to defend its autonomy from other sciences is reminiscent of the position once faced by sociology and linguistics, where Emile Durkheim and Ferdinand Saussure fought for their separation from psychology. In recent times, Franco Moretti has attempted to mimic the methodology of formalists, though he still advocates the stance of a methodologically opposed party, which assumes that literary facts can be explained using the logic of social sciences.